Shaping cross-sectoral cooperation based on smart specializations in the city of Zielona Góra = Kształtowanie współdziałania międzysektorowego w oparciu o inteligentne specjalizacje na przykładzie miasta Zielona Góra - Gębska, Karolina (Zielona Góra: Faculty of Economics and Management Press)
Among a big number of forms of relations, which the collaboration of a minimum of two entities may be based on, it is important in the context of the science and business environment to find a reference point connecting these entities. If it is necessary to integrate two sectors, this process is complex. The solution to this problem is to find a common point of reference. On the example of strengthening the ties between business and science sectors, the merging function is adopted by selected smart specializations in the European, national and regional areas.
Keywords: nauka; biznes; województwo lubuskie; inteligentne specjalizacje; Zielona Góra; science; business; Lubuskie voivodship; smart specialisations